Enhancing digital resilience through scratch-based mathematics in context learning among elementary students - Fahrudin, Fahrudin; Turmudi, Turmudi; Prabawanto, Sufiyani; Aras, Irianto (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: This study aimed to examine the effectiveness of Scratch-based Mathematics in Context (MiC) learning compared to conventional mathematics instruction in enhancing the digital resilience of fifth-grade elementary school students in East Lampung Regency. Method: A quasi-experimental design with a pretest–posttest control group was employed. The participants consisted of 52 fifth-grade students from two private Islamic elementary schools, with 26 students assigned to the experimental group and 26 students to the control group. The experimental group received Scratch-based MiC learning over six instructional sessions, while the control group received conventional mathematics instruction. Digital resilience was measured using the Digital Resilience Scale for Children (DRSC), and the data were analyzed using ANCOVA with pretest scores as the covariate. Findings: The results revealed that, after controlling for pretest scores, students in the experimental group achieved significantly higher posttest digital resilience scores than those in the control group (F(1,49) = 28.46, p < 0.001, η² = 0.37). The experimental group demonstrated a mean increase of 0.98 points (from 2.33 to 3.31), whereas the control group improved by only 0.30 points (from 2.34 to 2.64). The largest improvements were observed in the dimensions of technical problem-solving and digital logical thinking. Furthermore, no significant differences were found based on gender, indicating that the intervention was equally beneficial for male and female students. Significance: This study provides empirical evidence that integrating Scratch-based visual programming with Mathematics in Context learning can support the development of elementary students’ digital resilience. The findings contribute to mathematics education by demonstrating how contextual mathematical learning combined with programming activities can strengthen students’ ability to solve digital problems, think logically, adapt to technology, and respond constructively to digital challenges.